Pengaruh Alga Merah (Kappaphycus alvarezii) terhadap Mutu Ikan Kembung (Rastrelliger sp.) [ Effect of Red Algae (Kappaphycus alvarezii) on The Quality of Mackerel (Rastrelliger sp.)] - Wahju Tjahjaningsih; Ayu Lana Nafisyah; Rahayu Kusdarwati; Annur Ahadi Abdillah (Faculty of Fisheries and Marine Universitas Airlangga, 2015)
Abstract Kembung fish (Rastrelliger sp.) is a pelagic fish with high catching production volumes. The high catching volume require the fishermen and traders to maintain the quality of fish because fish is highly perishable product. Formalin abbuse as a substance to inhibit deterioration of fish induce natural substances exploration as formalin substitute in the field. One of these natural substances which widely cultivated in Indonesia is Kappaphycus alvarezii. This study aim to determine the effect of red algae (K.alvarezii) on the quality of kembung fish. The research method is experimental with a Completely Randomized Design (CRD). The treatment used is different soaking solution concentration, namely A (K.alvarezii 0%), B (K.alvarezii 25%), C (K.alvarezii 50%), D (K.alvarezii 75%) and E (formalin 1%) with four repetitions in each treatment. The primary parameters measured were the total bacterial count and organoleptic of kembung fish. The secondary parameters measured were pH of kembung fish meat. The data analyzed by Analysis of Variance (ANAVA) and the differences between treatments were determined by Duncan's Multiple Range Test. The results showed that the red algae (K.alvarezii) with concentrations 0%, 25%, 50% and 75% significantly (p<0,05) on the quality of kembung fish. K.alvarezii able to inhibit the bacterial growth, but the organoleptic value (visibility, odor and texture) is lower than formalin. Based on these results, further research is needed regarding the use of appropriate concentrations so that the quality of kembung fish maintained as before the treatment (either from the total bacterial count and organoleptic value).